(untitled) (Research, Society and Development, 2022)
The objective of this work was to study the epidemiology and distribution of equine sarcoid lesions diagnosed at the Laboratório Regional de Diagnóstico of UFPel (LRD/UFPel) over a period of 20 years, as well as to determine the main types and, the molecular identify of the bovine papillomavirus (BPV) associated to the lesions. Cases received between 2000 and 2020 were retrieved from the laboratory’s necropsy protocols. The paraffin blocks of each case were cut into 3-5µm sections, stained with hematoxylin and eosin (HE) and reassessed under an optical microscope. The samples sent to the laboratory in 2021 were fixed in 10% formalin for histopathology and immunohistochemistry and, an aliquot of frozen tissues were sent to the Laboratory of Virology and Immunology (LabVir/UFPel) for PCR. During the study period, 258 cases were diagnosed, of which 75.96% in the Crioula breed, mainly in horses aged two to five years (42.64%). The macroscopic characteristics associated with the histopathology allowed us to determine the type of sarcoid in each case. In 46.8% of the cases, the sarcoids were fibroblastic. Of the 258 cases, 61% were single, mainly observed in the limbs, and 32% were multiple, most often present in the trunk. The BPV genome was not detected by PCR and the IHC was negative for protein S-100 and positive for vimentin, allowing the differential diagnosis of other equine cutaneous neoplasms. The record of 258 cases of equine sarcoid for approximately 20 years has contributed significantly to understand its epidemiology in southern Rio Grande do Sul and revealed the importance of the disease in the studied region.